Peran Pengendali Pelatihan dalam Mencegah Stres pada Peserta Pendidikan Dasar CPNS - Agusttina Catur Setyaningrum (Balai Diklat Keagamaan Semarang, 2023)
Factors that may trigger stress during the basic training of civil servant candidates (Latsar CPNS) include changes in activities, learning processes, adjustments to technological capabilities, constraints of internet network, academic demands being too heavy, assignments piling up, and demands for graduation. This study uses a qualitative approach, aiming at knowing the role of Master of Training in preventing stress felt by the participants of the basic training at Bapelkes Semarang. Data collection techniques used is Interview and Focus Group Discussion. The results show that Master of Training had played a role in the stress prevention. This role is carried out through roles in the training preparation, training implementation and training evaluation. The roles carried out include conducting curriculum reviews, preparing learning scenarios/schedules, determining facilitators, preparing facilities and infrastructure, controlling the training process, providing motivation and support, being a liaison between the committee, participants and facilitators and helping participants achieve competency in the CPNS Latsar by means of provide evaluation-related information. The recommendation from this study is to continue to make Master of Training available in every training because of their proven role in preventing stress felt by participants.